Modeling proximalisation in axolotl limb regeneration - Hernán Arce; Alberto Sebastián Ceccarelli; Rodrigo Carlos Córdoba; Ana Catarina Rodrigues Oliveira; Maximina Hee Yun; Osvaldo Chara (Scientific Reports)
Abstract The axolotl (Ambystoma mexicanum) possesses a remarkable ability to regenerate tissues. Following limb amputation, a blastema of progenitor cells forms, expands, and reconstructs all distal structures, implying that mature cells near the wound retain positional memory along the proximal–distal (PD) axis. Key regulators of positional identity, such as Prod1 and Tig1, promote proximalisation—a shift toward a more proximal identity—when overexpressed, but the mechanisms governing this process remain unclear. In this study, we tracked changes in cellular density along the PD axis of regenerating axolotl limbs after transfecting distal blastemas with Tig1 and Prod1, mapping the spatiotemporal distribution of transfected cells and their progeny throughout regeneration. Using a continuous mathematical modelling approach, we predict a proximalisation velocity induced by factors eliciting proximal identity as Prod1 and Tig1, which is consistent with a proximalisation force driven by a positional potential. Our findings provide a foundational framework for understanding how cells acquire positional identity to guide limb regeneration in axolotls.